Treatment of Bone Loss With the Induced Membrane Technique: Techniques and Outcomes. Issue 12 (December 2015) - Taylor, Benjamin C.; Hancock, Jonathan; Zitzke, Ryan; Castaneda, Joaquin
Abstract : Objectives: To critically review the outcomes and issues associated with the induced membrane technique in a trauma population. Design: Retrospective case series, Level IV therapeutic study. Setting: Urban Level I trauma center. Patients: Sixty-nine patients aged 18 years or older who underwent treatment of bone loss with the induced membrane technique. Intervention: All patients underwent open treatment of their traumatic bone loss with a 2-stage induced membrane technique. Main Outcome Measurement: Bony union rate, as evaluated with radiographic and clinical signs of healing. Results: Patients in this series averaged 4.4 surgeries, which included initial debridement to definitive fixation. The tibia was the most common site of bone loss, encompassing 50.7% of the series, whereas femoral bone loss was next at 24.6%. Polymethylmethacrylate spacers were in place for a mean of 11.2 weeks (mode of 8 weeks) before bone grafting for an average bony defect volume of 76.6 cm 3 . Union was obtained in 82.6% of patients at a mean of 26.6 weeks after grafting. Mean follow-up for these patients was 23.8 months. Conclusions: The induced membrane technique is an effective method to obtain bony union when used in the trauma population. However, it is not foolproof, and attention must be paid to the critical subtleties of the procedure. Further investigation is needed to help determine the optimal spacer composition and other technical aspects of the procedure such as timing of the exchange. Level of Evidence: Therapeutic Level IV. See Instructions for Authors for a complete description of levels of evidence. Abstract : Supplemental Digital Content is Available in the Text.